Determinants of Small and Medium-Sized Enterprises’ Financing Demand in Saudi Arabia (1996-2020) - Althobaiti, Shrouq Saad; Bajaber, Nadia Ahmed (Journal of Economic, Administrative and Legal Sciences, 2025)
In light of Saudi Arabia’s Vision 2030, which emphasizes financing small and medium-sized enterprises (SMEs) to enhance their economic and social contributions and to transition toward sustainable economic development by increasing the proportion of financing, this study aimed to measure the determinants of SMEs’ demand for financing in Saudi Arabia. To achieve this, the study applied the Least Squares (LS) Method to estimate the demand function for the period from 1996 to 2020. The estimation results indicated that the relationship between the volume of currency in circulation and economic freedom with SMEs’ demand for financing is positive, while the relationship between interest rates and the demand for financing is inverse. Based on these findings, the study recommended conducting future research, provided the necessary data are available, to achieve more accurate results regarding the financing of SMEs in Saudi Arabia. It also called for increased academic attention to this area within Saudi Arabia, and for enhancing the contribution of academic research and studies related to it. Additionally, the study advocated for encouraging the banking sector to ease the conditions for granting loans and to adjust the loan sizes to align with the capabilities of these enterprises.